2019
DOI: 10.1371/journal.pbio.2006741
|View full text |Cite
|
Sign up to set email alerts
|

Simu-dependent clearance of dying cells regulates macrophage function and inflammation resolution

Abstract: Macrophages encounter and clear apoptotic cells during normal development and homeostasis, including at numerous sites of pathology. Clearance of apoptotic cells has been intensively studied, but the effects of macrophage–apoptotic cell interactions on macrophage behaviour are poorly understood. Using Drosophila embryos, we have exploited the ease of manipulating cell death and apoptotic cell clearance in this model to identify that the loss of the apoptotic cell clearance receptor Six-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 84 publications
1
53
0
Order By: Relevance
“…In vertebrates, a range of stimuli drive macrophage heterogeneity and polarisation [3,4], with apoptotic cells able to polarise macrophages towards anti-inflammatory phenotypes [50,51]. In the developing fly embryo, high apoptotic cell burdens impair wound responses [52,53], consistent with reprogramming of plasmatocytes towards less wound-responsive states. In order to test whether apoptotic cells might regulate plasmatocyte subpopulations, we exposed plasmatocytes to increased levels of apoptosis in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vertebrates, a range of stimuli drive macrophage heterogeneity and polarisation [3,4], with apoptotic cells able to polarise macrophages towards anti-inflammatory phenotypes [50,51]. In the developing fly embryo, high apoptotic cell burdens impair wound responses [52,53], consistent with reprogramming of plasmatocytes towards less wound-responsive states. In order to test whether apoptotic cells might regulate plasmatocyte subpopulations, we exposed plasmatocytes to increased levels of apoptosis in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptotic cell clearance can promote anti-inflammatory states in vertebrates [78]. Consequently, it is both consistent and compelling that exposure of Drosophila plasmatocytes to excessive levels of apoptotic cells dampens their inflammatory responses to injury and rates of migration in the developing embryo [18,52,53] and also shifts cells out of the more wound-responsive and potentially pro-inflammatory subpopulations we have discovered. Other precedents may be apparent in flies with shifts towards aerobic glycolysis occurring during infection [79], similar to those observed in vertebrate polarisation to pro-inflammatory states [80].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among the genes involved in phagocytosis, is a large panel of genes coding for transmembrane phagocytic receptors involved in pathogen recognition, such as the Nimrod family (Eater (Kocks et al, 2005), NimC1 (Kurucz et al, 2007) and NimC2), several scavenger receptors (Sr-CIV, He (Kurucz et al, 2003), Draper (Drpr) (Cuttell et al, 2008; Hashimoto et al, 2009), Peste (Philips et al, 2005)) as well as the integrins Scab (alpha-PS3) and Integrin beta-nu (Itgbn) (Nonaka et al, 2013). Noteworthy, the E16 embryonic hemocytes are specifically enriched for NimC4 (also called Simu), a receptor of the Nimrod family that is involved in the phagocytosis of apoptotic bodies ( Figure 1E ) (Kurant et al, 2008; Roddie et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A report showed that apoptosis participates in macrophage dispersal during development, with chronic high amounts of uncleared apoptotic cells and acute apoptosis induction impairing wound responses in experimental studies, without requiring phagocytosis of the dying cells 22 . This leads to weakened macrophage recruitment and www.nature.com/scientificreports www.nature.com/scientificreports/ decreased autophagy level.…”
Section: Discussionmentioning
confidence: 99%